2020
DOI: 10.1177/2058460120957295
|View full text |Cite
|
Sign up to set email alerts
|

The apparent diffusion coefficient is a useful biomarker in predicting treatment response in patients with locally advanced rectal cancer

Abstract: Background Apparent diffusion coefficient (ADC) values achieve promising results in treatment response prediction in patients with several types of cancers. Purpose To determine whether ADC values predict neoadjuvant chemoradiation treatment (nCRT) response in patients with locally advanced rectal cancer (LARC). Material and Methods Forty-four patients with LARC who underwent magnetic resonance imaging scans before and after nCRT followed by delayed surgery were enrolled retrospectively. The sample was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…ADC values may reflect cellularity, tissue perfusion, and necrosis (39,40). Both minimum and mean ADC values predicted treatment response in patients with locally advanced rectal cancer before neoadjuvant chemoradiation treatment (41). A recent meta-analysis showed that alterations between pre-and post-treatment ADC can identify responders to TACE in HCC (42).…”
Section: Discussionmentioning
confidence: 99%
“…ADC values may reflect cellularity, tissue perfusion, and necrosis (39,40). Both minimum and mean ADC values predicted treatment response in patients with locally advanced rectal cancer before neoadjuvant chemoradiation treatment (41). A recent meta-analysis showed that alterations between pre-and post-treatment ADC can identify responders to TACE in HCC (42).…”
Section: Discussionmentioning
confidence: 99%
“…ADC values obtained at DWI have been con rmed to be related to tumor cellularity, with lower ADC values associated with increased tumor cellularity [9]. However, these studies on the use of ADC values for treatment response evaluation are inconsistent [10][11][12][13][14]. These con icting results may partly be because the ADC values calculated from DWI are based on a mono-exponential decay model, which hypothesizes the free motion of water molecules following a Gaussian distribution [15].…”
Section: Introductionmentioning
confidence: 99%